The Relationship of The Environmental Sanitation With The Diarrhent Events in Children in Kawedekan Village, Balonggebang, Gondang District, Nganjuk Regency - Sri Dasih; Ardi Bastian (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2024)
Diarrhea is still one of the main causes of morbidity and death. Almost all geographical regions of the world and all age groups are attacked by diarrhea, but severe illness with high mortality is mainly found in infants and toddlers. The purpose of this study was to analyze the relationship of environmental sanitation with the incidence of diarrhea in infants in Kawedekan Hamlet, Balonggebang Village, Gondang District, Nganjuk Regency. The design of this study was an observational quantitative study with a cross sectional approach with the focus of the research directed to be to analyze the relationship of environmental sanitation with the incidence of diarrhea in infants in Kawedekan Hamlet Balonggebang Village Gondang District Nganjuk District with a population of 73 respondents and a sample of 62 respondents taken with Simple technique Random Sampling. The findings found that half the respondents had environmental sanitation in the less category as many as 31 respondents (50%). Most respondents did not experience diarrhea as many as 47 respondents (75.8%). The results of the study using the Chi Square Test showed that the p-value of 0.001 <0.05 then H1 was accepted so it was concluded that there was a relationship of environmental sanitation with the incidence of diarrhea in infants in Kawedekan Hamlet Balonggebang Village Gondang District Nganjuk District. Communities in Kawedekan Hamlet Balonggebang Village Gondang District Nganjuk Regency must be more concerned with environmental sanitation to create a healthy environment and avoid disease outbreaks